THOUGHTS ON XENOPHOBIA, DISRUPTIVE NATION AND "MAN ON GROUND" (The Strategic Review for Southern Africa, 2020)
Stories of Africans displaced by war taking high risks to get to an often inhospitable Western Europe are frequently in the news. But subSaharan Africa is the region which hosts the largest population of refugees in the world. Refugees who flee to sub Saharan African countries are also frequently subjected to xenophobic exclusion and violence by people who sometimes claim to be defending rights and privileges associated with national belonging. My aims are to point out new avenues for novel insights into the interrelations between xenophobia, disruption and nation by giving attractive detail and depth to the discussion using Director Akin Omotoso's Man on Ground (2011); putting forward arguments against xenophobic stereotypes and violence; pointing out some pitfalls of nation-building; and by finding and imagining human ground amidst disruptive nationhood. What is offered is a new synthesis of philosophical insights that defies distinctions between African and Western philosophy. Going beyond nativism and xenophobia, this synthesis speaks of the need and possibility to craft common human ground that enables people to become the most they can be.
Keywords: Western Europe; subSaharan Africa; Refugees; xenophobia; african philosophy; western philosophy; nativism